THE EFFECT OF PORPE AND QTA TECHNIQUES TOWARD STUDENTS’ READING PERSUASIVE SKILL - Rachmanita; Eva Saptarina (Universitas Islam Ogan Komering Ilir Kayuagung, 2018)
The objective of this study was to see whether the use of techniques as PORPE (Predict, Organize, Rehearse, Practice, and Evaluate) and QtA (Question the Author) were effective in improving students’ reading achievement or not. This study was experimental research with non- randomized control group pretest posttest design. The sample of this research was seventy five students of eleventh graders of social class at SMA Negeri 2 Kayuagung which consisted of three groups, two experimental groups and one control group. The first experimental group was given treatment by using PORPE technique, the second group was given treatment by using QtA technique, and the control group was not given treatment. The data were gathered by using reading test and were analyzed by using One-way ANOVA. The findings showed that PORPE and QtA techniques were effective in improving the students’ reading achievement